2015
DOI: 10.1161/strokeaha.115.010449
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Amyloid-β on Cognitive Decline After Stroke/Transient Ischemic Attack

Abstract: C ognitive impairment in the context of stroke or transient ischemic attack (TIA) is a prototype of vascular cognitive impairment (VCI). Our recent in vivo study using carbon-11-labeled Pittsburgh compound B ( 11 C-PiB) positron emission tomography (PET) found that ≈30% of subjects with poststroke/TIA cognitive impairment harbored Alzheimer's pathology.1 Although some studies suggested that in patients with clinical Alzheimer's disease (AD), comorbid cerebrovascular disease was associated with a more rapid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 31 publications
3
67
0
3
Order By: Relevance
“…Some rodent studies have found that the Aβ deposits could be induced shortly after stroke but vanish within a few weeks, possibly caused by an increased clearance of pre-existing Aβ deposits, suggesting that cerebrovascular lesions only induce transient but not permanent Aβ deposition (11,14). A clinical study using ELISA to examine serum Aβ levels found that serum Aβ 40 and Aβ 42 levels were increased at day 1, reached peak levels at day 3 and decreased to pre-stroke levels at day 7, indicating that the elevation of serum Aβ levels was also transient (27). In our study, no significant difference was found between monkeys with MCAO and controls in terms of Aβ 40 and, Aβ 42 levels, or the Aβ 40 /Aβ 42 ratio in CSF and plasma at 12 months after MCAO.…”
Section: Discussionmentioning
confidence: 99%
“…Some rodent studies have found that the Aβ deposits could be induced shortly after stroke but vanish within a few weeks, possibly caused by an increased clearance of pre-existing Aβ deposits, suggesting that cerebrovascular lesions only induce transient but not permanent Aβ deposition (11,14). A clinical study using ELISA to examine serum Aβ levels found that serum Aβ 40 and Aβ 42 levels were increased at day 1, reached peak levels at day 3 and decreased to pre-stroke levels at day 7, indicating that the elevation of serum Aβ levels was also transient (27). In our study, no significant difference was found between monkeys with MCAO and controls in terms of Aβ 40 and, Aβ 42 levels, or the Aβ 40 /Aβ 42 ratio in CSF and plasma at 12 months after MCAO.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, PINK1 has been shown to protect neurons from OGD-induced cell death (Zhao et al, 2013), while parkin depletion has been shown to contribute to neuronal death after focal ischemia (Mengesdorf et al, 2002). Furthermore, serum A β levels are a known predictor of short-term neurological deficits after stroke (Liu et al, 2015a) and patients with cerebral A β deposition show more severe and rapid cognitive decline after stroke (Liu et al, 2015b). Mutations or overexpression of α -Syn have been mostly implicated in the pathogenesis of PD, but α -Syn has also been reported to play a neuroprotective role under a cysteine-string protein- α -null-mediated neurodegenerative condition by maintaining synaptic integrity (Chandra et al, 2005; Ruiz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Progressive memory decline suggests superimposed Alzheimer disease pathology, and, in fact, underlying amyloid pathology was proposed as a key determinant of delayed cognitive decline in stroke survivors in a recent study [4]. In our study, memory was stable compared to executive function, which suggests that either patients with progressive memory decline were selectively lost during follow-up, or, contrary to the result of the previous study [4], delayed poststroke cognitive decline may not be due to Alzheimer pathology. Further studies should, therefore, explore the mechanisms of domain-specific longitudinal cognitive changes.…”
Section: Discussionmentioning
confidence: 99%
“…Though most stroke survivors have stable cognitive trajectories [3], some show a delayed cognitive decline [4]. Pathophysiology and clinical determinants of delayed poststroke cognitive decline might differ from those for cognitive impairments occurring relatively early after stroke, and underlying amyloid pathology was proposed as a key determinant of delayed cognitive decline in stroke survivors [4].…”
Section: Introductionmentioning
confidence: 99%